Last updated at May 29, 2018 by Teachoo
Transcript
Ex 3.3, 12 Prove that sin2 6 sin2 4 = sin 2 sin 10 Solving L.H.S. sin2 6x sin2 4x Using a2 b2 = (a + b) (a - b) = (sin 6x + sin 4x) (sin 6x sin 4x) Lets calculate (sin 6x + sin 4x) and (sin 6x sin 4x) separately Hence sin2 6x sin2 4x = (sin 6x + sin 4x) (sin 6x sin 4x) = (2 sin 5x cos x) (2 cos 5x sin x) = (2 sin 5x cos 5x) . (2 sin x cos x) = (sin 10x) (sin 2x) = R.H.S. Hence, L.H.S. = R.H.S. Hence proved
Ex 3.3
Ex 3.3, 2 Important
Ex 3.3, 3 Important
Ex 3.3, 4
Ex 3.3, 5 (i) Important
Ex 3.3, 5 (ii)
Ex 3.3, 6 Important
Ex 3.3, 7
Ex 3.3, 8 Important
Ex 3.3, 9 Important
Ex 3.3, 10
Ex 3.3, 11 Important
Ex 3.3, 12 You are here
Ex 3.3, 13 Important
Ex 3.3, 14
Ex 3.3, 15
Ex 3.3, 16 Important
Ex 3.3, 17
Ex 3.3, 18 Important
Ex 3.3, 19
Ex 3.3, 20
Ex 3.3, 21 Important
Ex 3.3, 22 Important
Ex 3.3, 23 Important
Ex 3.3, 24
Ex 3.3, 25
Ex 3.3
About the Author